Exploring Credit Risk Management and Financial Performance: Evidence from People’s Leasing and Finance PLC - Francis, S.J.; Hansamali, H.G.C.; Ganeshamoorthy, M.; Abarna, R. (Wayamba Journal of Management, 2024)
The stability and financial performance of the financial intermediaries play a pivotal role in creating the sustainable development of any modern-day economy. Lending is a fundamental income-generating activity of these financial institutions, yet there exists an element of risk in providing credit, that mainly stems from borrowers' failure in fulfilling their loan repayment obligations. Considering the profound impact of credit risk on financial performance, this study aims at examining the relationship between credit risk management indicators, namely risk identification, risk analysis, nonperforming loan (NPL) identification, capital adequacy, and financial performance of non-bank financial institutions. The data gathered through a structured questionnaire from a sample consisting of 152 employees serving the credit departments of selected branches of People's Finance and Leasing PLC in the Colombo district. The results of the multiple regression analysis indicate that risk identification and NPL identification have a positive and significant impact on financial performance. However, the impact of risk analysis and capital adequacy on financial performance were found to be insignificant, contrary to the findings of the previous studies which emphasize the importance of risk analysis and capital adequacy in ensuring financial stability. These results highlight the importance of effective risk identification and NPL management in enhancing financial performance. In conclusion, the study highlights that effective credit risk management practices, particularly in risk identification and NPL management, are crucial in enhancing the financial performance of non-bank financial institutions. Therefore, employing effective credit risk management strategies ensures achieving superior financial performance. Hence, financial institutions ought to allocate resources toward implementing sophisticated risk assessment tools that integrate both quantitative and qualitative data.
Keywords: Financial performance; Non-banking financial institutions; Risk identification; Non-performing loans; Capital adequacy